TAX AVOIDANCE MEMODERASI HUBUNGAN ANTARA KEPEMILIKAN ASING DAN INTANGIBLE ASSETS TERHADAP TRANSFER PRICING - Fina Fitriyana; Wiandy Putra Pratama (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Transfer pricing is a company policy in determining the price of transactions for goods or services between companies or parties that have a special relationship. Transfer pricing in this research is measured using Related Party Transactions or Receivables from related parties in non-primary consumer goods sector companies listed on the Indonesia Stock Exchange 2017-2022. This research aims to empirically test the influence of foreign ownership and intangible assets on transfer pricing with tax avoidance as a moderating variable. This type of research is quantitative research using secondary data from the company's annual report for the 2017-2022 period. The sampling method used purposive sampling, so that a research sample of 17 companies was obtained. The research results show that the foreign ownership variable has a negative effect on transfer pricing, intangible assets have no effect on transfer pricing, tax avoidance moderates and strengthens the relationship between foreign ownership and transfer pricing and tax avoidance is unable to moderate the relationship between intangible assets and transfer pricing.